Senile Cataract - Kumari, Ragni (Journal of Community Medicine and Health Solutions, 2024)
Cataracts may be described as the opacity of crystalline lenses present in the eye. The translucent crystalline lens is a part of the human eye. It possesses all the physical characteristics of a biconvex lens. The eye’s lens performs similar functions to a camera’s lens. The lens directs light rays entering the eye to the retina’s sensitive layers. Any factor that increases the absorption of scattering of light by the lens reduces its transparency. The opacity of the lens or its capsule, whether developmental or acquired, is called a cataract. Cataracts vary in degree of density and site and assume various forms. Cataract is the leading cause of reversible visual impairment and blindness globally. There are several classifications of cataracts based on morphologic and/or etiologic criteria. However, in epidemiologic studies, the simplified system of three types based on localization of lens opacities is most commonly used: Nuclear cataract is the most common type, followed by cortical cataract and posterior subcapsular cataract. This most prevalent form of acquired cataract, also known as an “age-related cataract,” affects people of both sexes equally and typically develops after age 50. More than 90% of people experience senile cataracts by age 70. Although one eye is almost always afflicted before the other, the disorder is typically bilateral. In the available literature, there is no mention of any such drug that could reverse the opacity of the lens (cataract) once it occurred and make it clear and transparent again. Only replacement of opaque lenses with artificial transparent Intraocular lens (IOL) is successful treatment of cataracts. This review focuses on senile cataracts and the best possible management of senile cataracts.